RELIABILITY PROGRAM AS PART OF A BUSINESS STRATEGY - Isaque Moyses Guimaraes; Efe Peter Iyomi; Olutayo Opeyemi Ogunmilua (International Journal of Innovations in Engineering Research and Technology, 2021)
Plant reliability is an essential factor for the world of investments and companies that are currently in line with Environmental, Social, and Governance (ESG) goals have been supported by investors around the world. This paper states a valuable implementation of a reliability process that creates engagement among stakeholders and decreases the life-cycle cost of a plant while the reliability increases. In addition, it suggests how to create a solid base with the support of different areas and tools that lead to an increase in the reliability of equipment, systems, and plants.